Composite material, preparation method thereof and zirconia-based slurry

By coating a ceramic layer containing a pore-forming agent and a glass layer that transforms at high temperatures onto a metal substrate, a porous structure is formed, which solves the problem of coating peeling or breakage of metal materials at high temperatures and achieves insulation protection and structural stability at high temperatures.

CN121393993AActive Publication Date: 2026-01-23SUNGROW ICARBON TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511958621.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-24
Publication Date
2026-01-23
Estimated Expiration
2045-12-24

AI Technical Summary

Technical Problem

In existing technologies, metal materials are prone to insulation failure at high temperatures due to coating peeling or breakage, which cannot effectively protect the substrate.

Method used

The design employs composite materials, including a matrix, a ceramic layer, and a glass layer. The ceramic layer contains a pore-forming agent, and the glass layer transforms into a molten state at high temperatures to form a porous structure to cope with thermal stress and prevent cracking. The ceramic layer is prepared using a zirconia-based slurry to enhance insulation.

Benefits of technology

It effectively prevents the ceramic layer from cracking at high temperatures, maintains insulation, blocks direct impact between open flame and the substrate, improves the high-temperature resistance of the substrate, avoids short circuits and oxidation, and enhances the overall structural integrity of the composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121393993A_ABST
    Figure CN121393993A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material, a preparation method of the composite material and zirconia-based slurry, and belongs to the technical field of conductive material heat insulation protection. The ceramic layer covers at least part of the surface of the base body; the ceramic layer comprises a pore-forming agent; the glass layer covers at least part of one side, deviating from the base body, of the ceramic layer; wherein the pore-forming agent is configured to be gasified when a first temperature T1 is reached; the glass layer is configured to at least partially transform into a molten glass body when a second temperature T2 is reached, and T2 > T1. The composite material disclosed by the invention can resist fragmentation and avoid direct impact of open fire on the matrix, so that the high-temperature resistance of the matrix is improved, and an insulation effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of electrically conductive material thermal insulation protection, in particular to a composite material, a preparation method thereof and a zirconia-based slurry. BACKGROUND

[0002] Metallic materials are substances mainly composed of metallic elements with crystal structure. The core feature is high strength, good plasticity and toughness, and can be processed into complex parts through various processes such as casting, forging and welding, which are indispensable basic materials in aerospace, automobile manufacturing, building structures and daily life. In some cases, for safety reasons, the metallic materials are often wrapped with coatings or other insulation methods, and the coating of the metallic materials may peel off or break. SUMMARY Therefore, the present application provides a composite material, aiming to solve the technical problem of insulation failure caused by fragmentation of the composite material under high temperature heating.

[0003] Another object of the present application is to provide a preparation method of the composite material, aiming to provide a preparation method of the composite material solving the above technical problems.

[0004] Another object of the present application is to provide a zirconia-based slurry, aiming to solve the technical problem of fragmentation of the ceramic layer at high temperature.

[0005] The present application provides a composite material, comprising: the composite material comprises: a substrate; a ceramic layer, the ceramic layer is arranged on at least part of the surface of the substrate; the ceramic layer comprises a pore-forming agent; a glass layer, the glass layer is arranged on at least part of the side of the ceramic layer away from the substrate; wherein, the pore-forming agent is configured to be gasified when reaching a first temperature T1; the glass layer is configured to be at least partially converted into a glass body in a molten state when reaching a second temperature T2, and T2>T1.

[0006] Optionally, in some embodiments of the present application, the first temperature T1 satisfies: 350℃≤T1≤450℃.

[0007] Optionally, in some embodiments of the present application, the second temperature T2 satisfies: 900℃≤T2≤1000℃.

[0008] Optionally, in some embodiments of the present application, the linear thermal expansion coefficient of the glass layer ranges from 13×10 -6 / K to 19×10 -6 / K.

[0009] Optionally, in some embodiments of the present application, the linear thermal expansion coefficient of the ceramic layer ranges from 10×10 -6 / K to 12×10-6 / K.

[0010] Optionally, in some embodiments of the present application, the linear thermal expansion coefficient of the substrate ranges from 10x10 -6 / K to 18x10 -6 / K.

[0011] Optionally, in some embodiments of the present application, the substrate is made of metal.

[0012] Optionally, in some embodiments of the present application, the thermal conductivity of the ceramic layer ranges from 2.0 W / m·K to 3.3 W / m·K.

[0013] As a second aspect of the present application, an embodiment of the present application provides a zirconia-based slurry for preparing the ceramic layer of the composite material as described above, the zirconia-based slurry comprises, in terms of mass fraction: a zirconia-based material, 50 parts to 70 parts; a pore-forming material, 5 parts to 15 parts; a first solvent, 20 parts to 30 parts; a first binder, 3 parts to 5 parts.

[0014] Optionally, in some embodiments of the present application, the zirconia-based material satisfies at least one of the following conditions: a) the zirconia-based material comprises one or more of zirconium dioxide, yttrium oxide stabilized zirconia, scandium oxide stabilized zirconia; b) the crystal structure of the zirconia-based material comprises tetragonal phase and / or cubic phase; c) the particle size of the zirconia-based material ranges from 0.1 μm to 0.5 μm.

[0015] Optionally, in some embodiments of the present application, the pore-forming material satisfies at least one of the following conditions: d) the pore-forming material comprises one or more of corn starch, polymethyl methacrylate; e) the particle size of the pore-forming material ranges from 0.3 μm to 0.5 μm.

[0016] Optionally, in some embodiments of the present application, the zirconia-based slurry comprises, in terms of mass fraction: a pore-forming material, 8 parts to 13 parts; and / or, the particle size of the pore-forming material ranges from 0.35 μm to 0.45 μm.

[0017] Optionally, in some embodiments of the present application, the first solvent includes water, or the first solvent includes one or more of anhydrous ethanol, methyl ethyl ketone, toluene, xylene, isopropyl alcohol, and terpineol.

[0018] Optionally, in some embodiments of the present application, the first binder includes one or more of polyvinyl butyral, polyvinyl alcohol, and ethyl cellulose.

[0019] As a third aspect of the present application, an embodiment of the present application provides a preparation method of the composite material as described above, the preparation method comprising: disposing a zirconia-based slurry on at least part of a surface of a substrate to form a ceramic layer; the thickness of the zirconia-based slurry ranges from 20 μm to 200 μm; disposing a glass slurry on at least part of a side of the ceramic layer away from the substrate to form a glass layer; the thickness of the glass slurry ranges from 50 μm to 300 μm; wherein the glass slurry includes, in terms of mass fraction: an oxide, 60 parts to 80 parts; a second solvent, 15 parts to 35 parts; a second binder, 3 parts to 7 parts; a dispersant, 1 part to 2 parts.

[0020] Optionally, in some embodiments of the present application, the oxide includes a first oxide and a second oxide; wherein the glass slurry satisfies at least one of the following conditions: f) the first oxide includes one or more of calcium oxide, aluminum oxide, and magnesium oxide; g) the second oxide includes one or more of silicon oxide, sodium oxide, bismuth oxide, boron oxide, titanium oxide, cerium oxide, barium oxide, strontium oxide, lithium oxide, and zinc oxide; h) the mass ratio of the first oxide to the second oxide ranges from (27-30):(33-39).

[0021] Optionally, in some embodiments of the present application, the second solvent includes water, or the second solvent includes one or more of anhydrous ethanol, methyl ethyl ketone, toluene, xylene, isopropyl alcohol, and terpineol.

[0022] Optionally, in some embodiments of the present application, the second binder includes one or more of polyvinyl butyral, polyvinyl alcohol, and ethyl cellulose.

[0023] Optionally, in some embodiments of the present application, the dispersant includes one or more of triethanolamine and polyacrylic acid.

[0024] The composite material of the present application is configured by the pore-forming agent to be gasified when reaching a first temperature T1; the glass layer is configured to be at least partially transformed into a molten glass when reaching a second temperature T2, and T2>T1, so that when the temperature of the composite material reaches the first temperature T1, the pore-forming agent at the location is gasified, the location of the pore-forming agent 201 is converted into a pore structure, which can cope with a certain thermal stress release and prevent the peeling or fragmentation of the ceramic layer at high temperature; when the composite material reaches the second temperature T2, the at least partially molten glass permeates into the pore structure to form a composite structure. The composite material can resist fragmentation and avoid direct impact of open flames on the substrate, thereby improving the high-temperature resistance of the substrate and playing an insulating role.

[0025] The preparation method of the composite material of the present application coats the zirconia-based slurry and the glass slurry on the surface of the substrate in sequence to form the ceramic layer and the glass layer, so that the composite material can resist fragmentation and avoid direct impact of open flames on the substrate, thereby improving the high-temperature resistance of the substrate and playing an insulating role.

[0026] The zirconia-based slurry of the present application is configured by the presence of the pore-forming material in the zirconia-based slurry, so that the ceramic layer formed has the pore-forming agent at the location, which is gasified under heat and converted into a pore structure, which can cope with a certain thermal stress release. BRIEF DESCRIPTION OF DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following will briefly introduce the drawings needed in the embodiment description. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can also be obtained by those skilled in the art without creative labor.

[0028] Figure 1 is a structural schematic diagram of the composite material provided by some embodiments of the present application; Figure 2 is a structural schematic diagram of the composite material after being heated, provided by some embodiments of the present application; Figure 3 is a main step schematic diagram of the preparation method provided by some embodiments of the present application; Figure 4 is an SEM diagram of the section of the composite material after 450℃ heat treatment provided by embodiment 1 of the present application; Figure 5 is a test method schematic diagram of the composite material provided by some embodiments of the present application.

[0029] Explanation of reference signs: 10, substrate; 20, ceramic layer; 201, pore-forming agent; 202, pore structure; 30, glass layer; 30', glass layer after being heated; 301, glass body in molten state; 401, composite structure. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only some of the embodiments of the present application, but not all the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work fall within the scope of the present application. In addition, it should be understood that the specific embodiments described herein are only for the purpose of illustration and explanation of the present application, and are not intended to limit the present application.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used in the description herein is for describing the specific embodiments only and is not intended to be limiting of the application. As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.

[0032] In the present application, the orientation words such as "upper" and "lower" are generally used to refer to the upper and lower positions of the device in the actual use or working state, and specifically refer to the directions of the drawing surface in the drawings; and "inner" and "outer" refer to the outline of the device. In addition, in the description of the present application, the term "comprising" means "including but not limited to". The terms first, second, third, etc. are only used as labels and do not impose numerical requirements or establish sequences.

[0033] In the present application, "and / or" describes the association relationship of the associated objects, which means that there can be three kinds of relationships, for example, A and / or B, which can represent the following cases: A exists alone, A and B exist together, and B exists alone. Wherein A and B can be singular or plural.

[0034] In the present application, "at least one" means one or more, and "multiple" means two or more. "One or more", "at least one of the following" or similar expressions mean any combination of these items, including any combination of single item or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can represent a, b, c, a-b (i.e. a and b), a-c, b-c, or a-b-c, wherein a, b, and c can be single or multiple.

[0035] Various embodiments of the application can exist in a range of forms; it should be understood that a range format is used only for convenience and brevity, and that it does not constitute a limitation of the scope of the application; accordingly, it should be construed that any and all sub-combinations of two or more of the recited ranges are specifically contemplated and are part of the present application. For example, where a range of from 1 to 6 is stated, it is explicitly contemplated that sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, and the like, are specifically contemplated and are part of the present application, as are individual numbers within the range, such as 1, 2, 3, 4, 5, and 6, as applicable. Additionally, whenever a numerical range is indicated, it is meant to include any cited numeral (fractional or integral) within the indicated range.

[0036] Referring to Figure 1 As shown in FIG. 1, as a first aspect, the composite material of the present application comprises a substrate 10 and a ceramic layer 20 and a glass layer 30. The ceramic layer 20 is disposed on at least part of the surface of the substrate 10; the ceramic layer 20 includes a pore-forming agent 201; the glass layer 30 is disposed on at least part of the side of the ceramic layer 20 away from the substrate 10.

[0037] In which, the pore-forming agent 201 is configured to be gasified when reaching a first temperature T1; the glass layer 30 is configured to be at least partially converted into a molten glass 301 when reaching a second temperature T2, and T2>T1.

[0038] Referring to Figure 2 As shown in FIG. 1, when the temperature of the composite material reaches the first temperature T1, the pore-forming agent 201 is converted into a pore structure 202, which is located in the ceramic layer 20; when the temperature of the composite material reaches the second temperature T2, the glass layer 30 is converted into a heated glass layer 30' after being heated, at least part of the heated glass layer 30' is converted into a molten glass 301, and at least part of the molten glass 301 penetrates into the pore structure 202. After the molten glass 301 penetrates into the pore structure 202, a glass melt is formed, so that the ceramic layer 20 is converted into a composite structure 401, that is, the composite structure 401 comprises a structure of a ceramic composite glass melt, the glass melt is located in the pore structure 202, and the glass melt entering the pore structure 202 is dispersed in the composite structure 401. It can be understood that the glass melt is a liquid.

[0039] With the above scheme, the pore-forming agent 201 is configured to be gasified when the first temperature T1 is reached, and the position where the pore-forming agent 201 is located is converted into the pore structure 202. When the temperature rises, the ceramic layer 20 is a solid layer attached to the surface of the substrate 10, which plays a barrier role for open flames and the substrate 10; while the pore-forming agent 201 decomposes at high temperature, the position where the pore-forming agent 201 is located forms a pore structure 202, which can release a certain thermal stress and prevent the ceramic layer 20 from being separated from the substrate 10 due to the fragmentation of the ceramic layer 20, thereby avoiding the short circuit caused by the rapid temperature rise of the contact interface of the substrate 10 at the position where the ceramic layer 20 and the substrate 10 are separated.

[0040] In some embodiments, the substrate 10 is a metal material, and the substrate 10 can be a metal material with high temperature resistance.

[0041] Specifically, the substrate 10 can be a copper bar, an aluminum bar, or the like. The substrate 10 can be a structural member mainly serving as a carrier in the overall structure, can be a sheet metal member serving as a support made of a metal sheet through stamping, bending, welding, or the like, or can be a cover member for covering, protecting, and beautifying the internal structure, or the like.

[0042] The thermal runaway of the power battery can cause spontaneous combustion in various forms, not only due to the combustion or pressure relief of the internal battery cell, but also due to the melting caused by the short circuit of the copper bar of the high-voltage connecting piece near the battery pack shell.

[0043] Due to the melting and lapping phenomenon with the metal member, all non-metal members inside the battery pack will burn. Generally, the battery pack shell material includes sheet metal materials, and the melting point of most of the sheet metal materials exceeds 1500°C. However, the melting of the heat-conducting shell is not caused by the melting of the high temperature of the thermal runaway, but is caused by the sudden increase in the local area temperature. The core reason is that during the thermal runaway process, due to the high-temperature burning of the outer insulation material, the high-temperature deformation and damage of the copper bar and the surrounding parts, the copper bar is short-circuited with the upper shell, a local instantaneous high temperature is formed, the upper shell is locally melted and perforated, and finally the open flame is discharged. Therefore, the insulation protection of the high-voltage connecting piece copper bar in the thermal runaway is one of the important guarantees for the stable operation of the power battery.

[0044] When the base body 10 is a copper busbar used in a battery pack, the battery pack is generally adapted to a corresponding battery system, and when the battery pack is in thermal runaway, the battery system sprays water or other cooling substances. If there is no glass layer 30, these substances can enter the pore structure 202, affecting the insulation of the composite material. When the glass layer 30 of the present application is present, at least part of the glass body 301 in the molten state enters the pore structure 202 when the composite material is heated, which can effectively prevent the cooling substances from entering the pore structure 202 and affecting the insulation of the composite material. The composite material protects the copper busbar from high-temperature deformation and damage under conditions such as high-temperature and open flame impact, and at the same time, the composite material keeps the copper busbar in an insulating state at high temperature, preventing local instantaneous short circuit caused by molten short circuit and thus preventing the base body 10 from being melted by high temperature. The composite material ensures that the protective coating has good insulation and oxidation resistance. The coating satisfies the insulation capacity of the voltage in normal use, and always maintains good insulation after burning and during burning, without arcing phenomenon.

[0045] It can be understood that the glass layer 30 is configured to at least partially transform into a glass body 301 in a molten state when reaching the second temperature T2, and the glass body 301 in the molten state penetrates into the pore structure 202, and the ceramic layer 20 in the composite material transforms into a composite structure 401. At high temperature, the battery pack is generally adapted to a corresponding battery cooling system, and water or other cooling substances are sprayed, and the glass body 301 in the molten state enters the pore structure 202, which can effectively prevent the cooling substances from entering the pore structure 202, form an active sealing barrier, maintain the insulation performance of the composite material, effectively block oxygen and water vapor in the air, prevent oxygen from contacting the base body 10, greatly slow down the oxidation process of the metal in the base body 10 at high temperature, avoid secondary damage or risks that may be caused by the violent vaporization of the medium such as water or chemical reaction with the high-temperature base body 10, and thus maintain the electrical conductivity and mechanical strength of the base body 10; at the same time, the composite structure 401 formed by the glass body 301 in the molten state entering the pore structure 202 has better fracture resistance, and the glass body 301 in the molten state can effectively passivate the crack tip of the ceramic layer 20 when penetrating into the pore structure 202, which hinders the expansion of the crack under stress, which enhances the toughness, thermal shock resistance and overall structural integrity of the entire protective layer under high-temperature working conditions, thereby reducing the stress caused by rapid temperature changes or external mechanical impact, and avoiding failure of the protective layer due to fragmentation.

[0046] The normal temperature of the energy storage device is about 40°C, and if thermal runaway occurs, gas leakage and open flame may occur. As the temperature rises, the pore-forming agent 201 decomposes to form the pore structure 202, and then the glass begins to melt.

[0047] In some embodiments of the present application, the first temperature T1 satisfies: 350℃≤T1≤450℃. T1 can be any value or a range value of any two of 350℃, 360℃, 370℃, 380℃, 390℃, 400℃, 410℃, 420℃, 430℃, 440℃, 450℃.

[0048] It can be understood that, in the case that the temperature of the composite material reaches the first temperature T1, the pore-forming agent 201 is decomposed by heat to form gas to escape, thereby converting the space where the pore-forming agent 201 is located into the pore structure 202, matching the linear thermal expansion coefficient of the copper bar, coping with certain thermal stress release, and playing a role of blocking the open flame and the base body 10.

[0049] In some embodiments of the present application, the second temperature T2 satisfies: 900℃≤T2≤1000℃. T2 can be any value or a range value of any two of 900℃, 910℃, 920℃, 930℃, 940℃, 950℃, 960℃, 970℃, 980℃, 990℃, 1000℃.

[0050] It can be understood that, in the case that the temperature of the composite material reaches the second temperature T2, at least part of the glass layer 30 is converted into the molten glass body 301, and the molten glass body 301 penetrates into the pore structure 202. Glass is an amorphous substance, and as the temperature continues to rise, the hardness of the glass layer 30 gradually decreases, at least part of the glass layer 30 is converted into the molten glass body 301, and the molten glass body 301 penetrates into the pore structure 202, which can match the linear thermal expansion coefficient of the copper bar to avoid peeling of the glass layer 30 at high temperature. The peeling of the glass layer 30 can cause the peeling of the ceramic layer 20; at the same time, the molten glass body 301 can effectively prevent the cooling substance generated after the triggering of the cooling system from entering the pore structure 202, affecting the insulation of the composite material. When the temperature continues to rise, the temperature higher than 1000℃ can also continue to penetrate.

[0051] In some embodiments of the present application, the linear thermal expansion coefficient of the glass layer 30 is in the range of 13×10 -6 / K to 19×10 -6 / K; the linear thermal expansion coefficient of the ceramic layer 20 is in the range of 10×10 -6 / K to 12×10 -6 / K; and the linear thermal expansion coefficient of the base body 10 is in the range of 10×10 -6 / K to 18×10 -6 / K.

[0052] It can be understood that the linear thermal expansion coefficient of the glass layer 30 can be: 13×10 -6 / K, 14×10 -6Any value of K, 15 x 10 -6 Any value of K, 16 x 10 -6 Any value of K, 17 x 10 -6 Any value of K, 18 x 10 -6 Any value of K, 19 x 10 -6 Any value of K, 15 x 10 -6 Any value of K, 11 x 10 -6 Any value of K, 12 x 10 -6 Any value of K, 11 x 10 -6 Any value of K, 12 x 10 -6 Any value of K, 13 x 10 -6 Any value of K, 14 x 10 -6 Any value of K, 15 x 10 -6 Any value of K, 16 x 10 -6 Any value of K, 17 x 10 -6 Any value of K, 18 x 10 -6 Any value of K, 19 x 10 -6 Any value of K, 19 x 10

[0053] It can be understood that, due to the high linear thermal expansion coefficient of the substrate 10 of the present application, the linear thermal expansion coefficient of the glass layer 30 is close to that of the substrate 10, at high temperature, the molten glass 301 enters the hole structure 202, the linear thermal expansion coefficient of the composite structure 401 is adapted to the linear thermal expansion coefficient of the substrate 10, which can effectively slow down the peeling of the composite structure 401 and the substrate 10 at high temperature. The linear thermal expansion coefficient of the glass layer 30 is matched with the substrate 10, the zirconia provides high temperature resistance and heat insulation performance, and the hole structure 202 of the ceramic layer 20 can also provide expansion and contraction amount; the molten glass 301 penetrates into the hole structure 202 to form the composite structure 401, which can also provide good peeling resistance.

[0054] Specifically, when the substrate 10 is a copper bar, the linear thermal expansion coefficient of the glass layer 30 is close to that of the copper bar, at high temperature, the molten glass 301 enters the hole structure 202, the linear thermal expansion coefficient of the composite structure 401 is adapted to the linear thermal expansion coefficient of the copper bar, which can effectively slow down the peeling of the composite structure 401 and the copper bar at high temperature.

[0055] In some embodiments of the present application, the thermal conductivity of the ceramic layer 20 ranges from 2.0 W / m·K to 3.3 W / m·K. The thermal conductivity of the ceramic layer 20 can be any of 2.0 W / m·K, 2.1 W / m·K, 2.2 W / m·K, 2.3 W / m·K, 2.4 W / m·K, 2.5 W / m·K, 2.6 W / m·K, 2.7 W / m·K, 2.8 W / m·K, 2.9 W / m·K, 3.0 W / m·K, 3.1 W / m·K, 3.2 W / m·K, 3.3 W / m·K or a range of any two of them.

[0056] It can be understood that the ceramic layer 20 has thermal insulation properties, which can prevent the substrate 10 from being heated too quickly, inhibit the mismatch between the substrate 10 and the ceramic layer 20, and effectively slow down the peeling or breaking of the ceramic layer 20. Specifically, since copper has a high linear thermal expansion coefficient, the linear expansion is too fast during rapid heating, which can cause a mismatch problem with the protective coating. When the substrate 10 is a copper bar, the low thermal conductivity of the ceramic layer 20 can prevent the copper bar from being heated too quickly, and inhibit the peeling or breaking of the protective coating.

[0057] In some embodiments of the present application, the ceramic layer 20 and the glass layer 30 are insulators at room temperature, and the electrical resistivity ranges from 10 10 Ω·cm to 10 12 Ω·cm, and the composite material still has insulation capability at 10 kV. Of course, in actual applications, the composite material in the embodiments of the present application can be stacked in multiple layers to form a thicker coating to achieve better insulation and fire resistance.

[0058] It can be understood that the ceramic layer 20 and the glass layer 30 of the present application are insulators at room temperature, have insulation and oxidation resistance, and can protect the substrate 10 from safety problems caused by leakage or aging of the substrate 10.

[0059] As a second aspect of the present application, the embodiments of the present application provide a zirconia-based slurry for preparing the ceramic layer 20 of the composite material as described above, and the zirconia-based slurry comprises, by mass fraction: a zirconia-based material, 50 parts to 70 parts; a pore-forming material, 5 parts to 15 parts; a first solvent, 20 parts to 30 parts; a first binder, 3 parts to 5 parts.

[0060] It can be understood that the zirconia-based slurry includes the zirconia-based material, the pore-forming material, the first solvent, and the first binder by mass fraction. The zirconia-based slurry provided in the application is conducive to forming a stable ceramic layer 20, so that the ceramic layer 20 plays a barrier role for the open fire and the base body 10; and the first solvent and the first binder make the pore-forming agent 201 dispersed in the ceramic layer 20, which is conducive to forming a dispersed pore structure 202 at the position of the pore-forming agent 201 at high temperature, and can cope with the release of a certain thermal stress.

[0061] In some embodiments of the application, the zirconia-based material satisfies at least one of the following conditions: a) The zirconia-based material includes one or more of zirconium dioxide, yttrium oxide stabilized zirconia, and scandium oxide stabilized zirconia; b) The crystal structure of the zirconia-based material includes tetragonal phase and / or cubic phase; c) The particle size of the zirconia-based material ranges from 0.1 μm to 0.5 μm.

[0062] It can be understood that the zirconia-based material disperses the pore-forming material, which decomposes to form a ceramic layer 20 with a pore structure 202 at high temperature, can cope with the release of a certain thermal stress, plays a barrier role for the open fire and the copper bar, and reduces the peeling of the ceramic layer 20 and the base body 10 under the impact of continuous open fire.

[0063] In some embodiments of the application, the pore-forming material satisfies at least one of the following conditions: d) The pore-forming material includes one or more of corn starch and polymethyl methacrylate; e) The particle size of the pore-forming material ranges from 0.3 μm to 0.5 μm.

[0064] It can be understood that the pore-forming material is conducive to decomposition after being heated, and is conducive to forming a dispersed pore structure 202 at the position of the pore-forming agent 201 at high temperature.

[0065] In some embodiments of the application, the zirconia-based slurry includes, by mass fraction: The pore-forming material, 8 parts to 13 parts; And / or, the particle size of the pore-forming material ranges from 0.35 μm to 0.45 μm. The particle size of the pore-forming material can be any value or a range value of any two of 0.35 μm, 0.36 μm, 0.37 μm, 0.38 μm, 0.39 μm, 0.40 μm, 0.41 μm, 0.42 μm, 0.43 μm, 0.44 μm, and 0.45 μm.

[0066] In some embodiments of this application, the first solvent includes water, or the first solvent includes one or more of anhydrous ethanol, methyl ethyl ketone, toluene, xylene, isopropanol, and terpineol.

[0067] Understandably, the first solvent selection can be either water-based or oil-based, and the corresponding binder can also be adapted to the choice of solvent.

[0068] In some embodiments of this application, the first adhesive includes one or more of polyvinyl butyral, polyvinyl alcohol, and ethyl cellulose.

[0069] It is understandable that the first binder and the first solvent are both water-based or oil-based, in order to disperse the zirconia-based material and improve the stability of the zirconia-based slurry.

[0070] Reference Figure 3 As shown, as a third aspect, the method for preparing the composite material of this application includes the following steps: S100: A ceramic layer 20 is formed by depositing a zirconia-based slurry onto at least a portion of the surface of the substrate 10; the thickness of the zirconia-based slurry ranges from 20 μm to 200 μm. The thickness of the zirconia-based slurry can be any value or a range of any two of the following: 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, and 200 μm.

[0071] S200: A glass slurry is deposited on at least a portion of the ceramic layer 20 on the side opposite to the substrate 10 to form a glass layer 30; the thickness of the glass slurry ranges from 50 μm to 300 μm. The thickness of the glass slurry can be any value or a range of any two of the following: 50 μm, 80 μm, 110 μm, 140 μm, 170 μm, 200 μm, 230 μm, 260 μm, 290 μm, and 300 μm.

[0072] The zirconia-based slurry, by mass parts, includes: Zirconia-based material, 50 to 70 parts; Hole-forming material, 5 to 15 parts; First solvent, 20 to 30 parts; First adhesive, 3 to 5 parts; Glass slurry, by weight, includes: Oxides, 60 to 80 parts; Second solvent, 15 to 35 parts; Second adhesive, 3 to 7 parts; dispersant, 1 to 2 parts.

[0073] It can be understood that the zirconia-based slurry contains zirconia-based material, pore-forming material, first solvent, and first binder by mass fraction. The zirconia-based slurry provided in the present application is conducive to forming a stable ceramic layer 20, so that the ceramic layer 20 plays a barrier role for the open fire and the base body 10; and the first solvent and the first binder make the pore-forming agent 201 disperse in the ceramic layer 20, which is conducive to forming a dispersed pore structure 202 at the position of the pore-forming agent 201 at high temperature, and can cope with a certain thermal stress release.

[0074] It can be understood that the value of the fraction of the pore-forming material by mass fraction in the present application includes any value or a range value of any two of 5, 8, 10, 12, and 15. The fraction of the pore-forming material by mass fraction in the present application is conducive to the pore-forming material being converted into a pore structure 202 under high temperature heating, and provides a certain buffer range for the expansion and contraction of the ceramic layer 20. If the proportion of the pore-forming material is too low, too few pores cannot play a buffering role in the expansion or contraction process, and in the presence of the glass layer 30, the infiltration of the molten glass body 301 cannot be met; too much pore-forming agent 201 will cause the structure to collapse after sintering, affecting the mechanical strength of the ceramic layer 20 itself.

[0075] At the same time, the ceramic layer 20 is formed by coating the slurry formed by ceramic particles, and the ceramic particles have a certain gap between them. When the pore-forming agent 201 decomposes, the gas generated by the pore-forming agent 201 can also escape through the gap between the ceramic particles.

[0076] In some embodiments of the present application, in S100, the zirconia-based slurry is coated on at least part of the surface of the base body 10 to form the ceramic layer 20, which can be coated by flow casting, pulling and dipping, spin coating, screen printing and the like. The wet film thickness of the zirconia-based slurry is 50 μm to 200 μm.

[0077] In some embodiments of the present application, in S200, the glass slurry is coated on at least part of the side of the ceramic layer 20 away from the base body 10, which can be coated by flow casting, pulling and dipping, spin coating, screen printing and the like. The wet film thickness of the glass slurry is 50 μm to 300 μm.

[0078] In some embodiments of the present application, before the step S100, a plasma device can also be used to clean the surface of the copper bar, remove surface oil and other organic matter, and passivate the surface of the copper material to increase its adhesion to the coated slurry.

[0079] In some embodiments of the present application, the zirconia-based material satisfies at least one of the following conditions: a) the zirconia-based material comprises one or more of zirconia, yttria-stabilized zirconia, scandia-stabilized zirconia; b) the crystal structure of the zirconia-based material comprises tetragonal phase and / or cubic phase; c) the particle size of the zirconia-based material ranges from 0.1 pm to 0.5 pm.

[0080] It can be understood that the zirconia-based material is dispersed with the pore-forming material, the pore-forming material is decomposed at high temperature to form the ceramic layer 20 with the pore structure 202, which can cope with the release of certain thermal stress, play a role in blocking the open flame and the copper row, and reduce the peeling of the ceramic layer 20 and the substrate 10 under the impact of the continuous open flame.

[0081] It can be understood that the particle size of the zirconia-based material includes any value or range value of any two of 0.1 pm, 0.2 pm, 0.3 pm, 0.4 pm, and 0.5 pm. The zirconia-based material is the core material of the ceramic layer 20, and the zirconia-based material forms regular crystals at high temperature. Therefore, the appropriate zirconia-based material is conducive to forming a stable ceramic layer 20, thereby forming a support for the pore structure 202.

[0082] The pore-forming material satisfies at least one of the following conditions: d) the pore-forming material comprises one or more of corn starch and polymethyl methacrylate; e) the particle size of the pore-forming material ranges from 0.3 pm to 0.5 pm.

[0083] It can be understood that the pore-forming material is conducive to decomposition after being heated, and is conducive to forming a dispersed pore structure 202 at the location of the pore-forming agent 201 at high temperature.

[0084] It can be understood that the particle size of the pore-forming material of the present application includes any value or range value of any two of 0.30 pm, 0.35 pm, 0.40 pm, 0.45 pm, and 0.50 pm. The particle size of the pore-forming material of the present application is conducive to forming the pore structure 202, and the particle size is uniform and the pore distribution is uniform. If the particle size of the pore-forming material is too large, the pore structure 202 formed after sintering of the pore-forming material is easy to collapse. If the particle size of the pore-forming material is too small, it is not conducive to forming a pore structure 202 with uniform particle size and uniform pore distribution, which affects the infiltration of the glass body 301 in the molten state, and ultimately affects the fitting effect of the composite structure 401.

[0085] In some embodiments of the present application, the zirconia-based slurry comprises, by mass fraction: the pore-forming material, 8 parts to 13 parts.

[0086] In some embodiments of the present application, the pore-forming material has a particle size in the range of 0.35 μm to 0.45 μm. The particle size of the pore-forming material of the present application includes any value of 0.35 μm, 0.36 μm, 0.37 μm, 0.38 μm, 0.39 μm, 0.40 μm, 0.41 μm, 0.42 μm, 0.43 μm, 0.44 μm, 0.45 μm or a range value of any two thereof.

[0087] In some embodiments of the present application, the oxide includes a first oxide and a second oxide. The glass paste satisfies at least one of the following conditions: f) The first oxide includes one or more of calcium oxide, aluminum oxide, magnesium oxide; g) The second oxide includes one or more of silicon oxide, sodium oxide, bismuth oxide, boron oxide, titanium oxide, cerium oxide, barium oxide, strontium oxide, lithium oxide, zinc oxide; h) The mass ratio of the first oxide to the second oxide is in the range of (27-30):(33-39). The mass ratio of the first oxide to the second oxide includes any value of 27:33, 28:34, 29:35, 30:36, 27:37, 28:38, 29:39, 30:39 or a range value of any two thereof.

[0088] It can be understood that the linear thermal expansion coefficient of the first oxide is adapted to the substrate 10, which can effectively slow down the peeling of the composite structure 401 from the substrate 10 at high temperature.

[0089] It can be understood that the silicon oxide and the boron oxide act as network formers; the sodium oxide, the lithium oxide, the barium oxide and the strontium oxide act as network modifiers, the aluminum oxide, the titanium oxide and the zinc oxide act as intermediates, and the bismuth oxide and the cerium oxide act as additives, which can play their respective special roles in the glass and can be combined according to different requirements. For example, the sodium oxide provides oxygen ions, breaks the silicon-oxygen network, and significantly reduces the melting temperature, viscosity and softening point of the glass; the boron oxide can independently form a glass network, which can reduce the melting temperature and the linear thermal expansion coefficient, and improve the thermal stability and chemical stability; the lithium oxide is a strong fluxing agent, which can more significantly reduce the viscosity and the linear thermal expansion coefficient than the sodium oxide.

[0090] In some embodiments of the present application, the first solvent includes water, or the first solvent includes one or more of anhydrous ethanol, methyl ethyl ketone, toluene, xylene, isopropyl alcohol and terpilenol.

[0091] It can be understood that the first solvent can be selected from water-based solvents or oil-based solvents, and the corresponding binder can also be adapted to the selection of the solvent.

[0092] In some embodiments of the present application, the first binder comprises one or more of polyvinyl butyral, polyvinyl alcohol, and ethyl cellulose.

[0093] It can be understood that the first binder and the first solvent are water-based or oil-based, so as to disperse the zirconia-based material and improve the stability of the zirconia-based slurry.

[0094] In some embodiments of the present application, the second solvent comprises water, or the second solvent comprises one or more of anhydrous ethanol, methyl ethyl ketone, toluene, xylene, isopropyl alcohol, and terpineol.

[0095] It can be understood that the second solvent can be selected as a water-based solvent or an oil-based solvent, and the corresponding binder can be adapted to the selection of the solvent.

[0096] In some embodiments of the present application, the second binder comprises one or more of polyvinyl butyral, polyvinyl alcohol, and ethyl cellulose.

[0097] It can be understood that the second binder and the second solvent are water-based or oil-based, so as to disperse the zirconia-based material and improve the stability of the zirconia-based slurry.

[0098] In some embodiments of the present application, the dispersant comprises one or more of triethanolamine or polyacrylic acid.

[0099] It can be understood that the addition of the dispersant is beneficial to improve the uniformity of the slurry, reduce the aggregation of the powder material, prevent cracking, and increase the mechanical strength of the ceramic layer 20.

[0100] In some embodiments of the present application, the substrate 10 of the present application comprises a conductive copper piece or a copper material.

[0101] In some embodiments of the present application, the substrate 10 of the present application can be one or more of a pure metal or an alloy.

[0102] It can be understood that the conductive copper piece or the copper material, which needs to work in a high-temperature environment or needs to be fireproof, such as the copper bar material quality of the high-voltage connecting piece of the battery pack shell in an electric vehicle, can adopt the composite material of the present application. The substrate 10 can be selected from red copper, brass, and other copper materials.

[0103] The present application is further described below through specific embodiments.

[0104] Example 1 Step 1: Clean the surface of the copper bar using a plasma device to remove surface oil and other organic matter; Step 2: 60 parts of zirconia with primary particle size of 0.3 μm, 10 parts of pore-forming material corn starch, 22 parts of solvent ethanol, methyl ethyl ketone mixture (ethanol: methyl ethyl ketone = 1:1), 3 parts of binder polyvinyl butyral, the component materials are mixed in proportion to obtain zirconia-based slurry, the particle size of the pore-forming material is 0.4 μm; Step 3: the zirconia-based slurry is coated on the surface of the copper bar in a casting method, and the wet film thickness is 200 μm.

[0105] Step 4: standing at room temperature for 3 hours to naturally volatilize the solvent to obtain a composite material covered with a ceramic layer 20.

[0106] Step 5: 25 parts of silicon oxide, 15 parts of calcium oxide, 5 parts of sodium oxide, 3 parts of boron oxide, 7 parts of aluminum oxide, 5 parts of magnesium oxide, 7 parts of solvent ethanol, 13 parts of methyl ethyl ketone, 3 parts of polyvinyl butyral, 1 part of dispersant triethanolamine, the components are mixed in proportion to obtain a glass slurry.

[0107] Step 6: the glass slurry is coated on the surface of the ceramic layer 20 in a casting method, and the wet film thickness is 100 μm.

[0108] Step 7: natural volatilization at room temperature to obtain a composite material with a glass layer 30.

[0109] Figure 4 The SEM image of the composite material provided for Example 1 after heat treatment at 450°C. It can be seen from Figure 4 that the lowermost part of the picture is the substrate 10, specifically the copper bar, the composite structure 401 in the middle part has a hole structure 202 relative to the lowermost part of the substrate 10, and the uppermost part is the glass layer 30' after heating.

[0110] Example 2 The difference between this example and Example 1 is that the portion of the pore-forming material in Step 2 is 3 parts.

[0111] Example 3 The difference between this example and Example 1 is that the portion of the pore-forming material in Step 2 is 5 parts.

[0112] Example 4 The difference between this example and Example 1 is that the portion of the pore-forming material in Step 2 is 8 parts.

[0113] Example 5 The difference between this example and Example 1 is that the portion of the pore-forming material in Step 2 is 12 parts.

[0114] Example 6 The difference between this example and Example 1 is that the portion of the pore-forming material in Step 2 is 15 parts.

[0115] Example 7 This example differs from Example 1 in that the pore forming material in Step 2 is 18 parts.

[0116] Example 8 This example differs from Example 1 in that the pore forming material in Step 2 has a particle size of 0.2 μm.

[0117] Example 9 This example differs from Example 1 in that the pore forming material in Step 2 has a particle size of 0.3 μm.

[0118] Example 10 This example differs from Example 1 in that the pore forming material in Step 2 has a particle size of 0.5 μm.

[0119] Example 11 This example differs from Example 1 in that the pore forming material in Step 2 has a particle size of 0.7 μm.

[0120] Example 12 This example differs from Example 1 in that the zirconia-based material in Step 2 is 45 parts.

[0121] Example 13 This example differs from Example 1 in that the zirconia-based material in Step 2 is 50 parts.

[0122] Example 14 This example differs from Example 1 in that the zirconia-based material in Step 2 is 55 parts.

[0123] Example 15 This example differs from Example 1 in that the zirconia-based material in Step 2 is 65 parts.

[0124] Example 16 This example differs from Example 1 in that the zirconia-based material in Step 2 is 70 parts.

[0125] Example 17 This example differs from Example 1 in that the zirconia-based material in Step 2 is 75 parts.

[0126] Example 18 This example differs from Example 1 in that the zirconia-based material in Step 2 has a particle size of 0.1 μm.

[0127] Example 19 This example differs from Example 1 in that the zirconia-based material in Step 2 has a particle size of 0.2 μm.

[0128] Example 20 The difference between this example and Example 1 is that the particle size of the zirconia-based material in Step 2 is 0.4 μm.

[0129] Example 21 The difference between this example and Example 1 is that the particle size of the zirconia-based material in Step 2 is 0.5 μm.

[0130] Example 22 The difference between this example and Example 1 is that in Step 5, 30 parts of silicon oxide, 13 parts of calcium oxide, 4 parts of sodium oxide, 5 parts of boron oxide, 7 parts of aluminum oxide, and 10 parts of magnesium oxide are used.

[0131] Example 23 The difference between this example and Example 1 is that in Step 5, the amount of magnesium oxide is 2 parts.

[0132] Comparative Example 1 The difference between this comparative example and Example 1 is that there is no glass layer 30, i.e., Steps 5 and 6 are omitted.

[0133] Comparative Example 2 The difference between this comparative example and Example 1 is that there is no ceramic layer 20, i.e., Steps 2, 3, and 4 are omitted.

[0134] Comparative Example 3 The difference between this comparative example and Example 1 is that the order of the ceramic layer 20 and the glass layer 30 is reversed, i.e., Steps 5 and 6 are performed first, and then Steps 2, 3, and 4 are performed.

[0135] Test Method: Flame Jet Fire Impact Test: An SG003 spray gun produced by Zhejiang Focus Cigarette Accessories Co., Ltd. is used to roast the surface of the coating. As shown in FIG. 2B, under the condition that the composite material is heated, the location of the pore-forming agent 201 is converted into a pore structure 202, and the pore structure 202 is located in the ceramic layer 20; under the condition that the composite material is heated, at least part of the glass layer 30 is converted into a molten glass body 301, and at least part of the molten glass body 301 penetrates into the pore structure 202. The ceramic layer 20 in which the pore structure 202 is penetrated by the molten glass body 301 forms a composite structure 401. Figure 5

[0136] ​Insulation capability test result: the sample material is tested by using a voltage breakdown tester (output voltage 0~100kV, voltage rising rate 200V / s). The test material in the application is tested by using a stage voltage test method, the fixed voltage rising intensity, the initial test voltage is 2kV (the initial voltage is 20% of the expected breakdown voltage 10kV), after stopping for about 10 seconds, continue to rise to 4kV at the rate of 200V / s, and stop for 10 seconds. Repeat this stage for 5 cycles to finally reach 10kV, and stop for 10 seconds without breakdown of the sample, which meets the product requirements. If dielectric breakdown occurs during the stop period, the last stage voltage is the dielectric breakdown strength.

[0137] The partial parameters of the examples and the comparative examples of the application are shown in Table 1.

[0138] Table 1 Partial parameters of examples and comparative examples of the application

[0139] As can be seen from example 1 and comparative examples 1 to 3, when the composite structure 401 of the application is used, the position of the pore-forming agent 201 is converted into a pore structure 202 under the condition of heating of the composite material. When the temperature rises, the ceramic layer 20 is a solid layer attached to the surface of the substrate 10, which plays a barrier role for the open flame and the substrate 10; while the pore-forming agent 201 decomposes at high temperature, the position forms a pore structure 202, which can cope with the release of certain thermal stress. The composite material is resistant to high temperature, insulates heat and anti-cracking, which can avoid the direct impact of the open flame on the substrate 10, thereby improving the high temperature resistance of the substrate 10. The coating of example 1 does not crack and peel off after the flame gun open flame impact test, and the coating is not broken down in the insulation capability test. The protective coating of comparative example 1 cracks and peels off; the protective coating of comparative example 2 peels off in a molten state; the protective coating of comparative example 3 peels off, and the coatings of comparative examples 1 to 3 are all broken down.

[0140] As can be seen from examples 1 to 7 of the application, when the zirconia-based slurry includes 5 to 15 parts of pore-forming material by mass fraction, the protective coating of the coating does not crack in the flame gun open flame impact test, and the coating is not broken down in the insulation capability test. In the application, the fraction of the pore-forming material by mass fraction is beneficial to the conversion of the pore-forming material into a pore structure 202 under high temperature heating, which provides a certain buffer range for the expansion and contraction of the ceramic layer 20. When the fraction of the pore-forming material in example 3 is too low and the fraction of the pore-forming material in example 6 is too high, the protective coating cracks and peels off, and the coating is broken down in the insulation capability test.

[0141] As shown in Examples 1, 8 to 11, the particle size of the pore-forming material ranges from 0.3 μm to 0.5 μm. The particle size of the pore-forming material in this application is conducive to forming the pore structure 202, and the uniform particle size and pore distribution facilitate the penetration of the molten glass 301. The coating did not crack or peel off during the flame impact test, and the coating was not penetrated during the insulation test. In Example 8, the particle size of the pore-forming material was too small, and in Example 11, the particle size was too large. During the flame impact test, the protective coating of the coating cracked slightly but did not peel off, and the coating was penetrated during the insulation test.

[0142] Comparing Examples 1, 12 to 17, the zirconia-based slurry provided in this application facilitates the formation of a stable ceramic layer 20, which acts as a barrier against open flame and the substrate 10. When the amount of zirconia-based material in the zirconia-based slurry is between 50 and 70 parts by mass, the coating does not crack or peel off after a flame impact test, and the coating is not penetrated during the insulation test. In Example 12, the amount of zirconia-based material was too low, and in Example 17, the amount of zirconia-based material was too high. During the flame impact test, the protective coating of the coating cracked slightly but did not peel off, and the coating was penetrated during the insulation test.

[0143] Compared with Examples 1, 18 to 21, the particle size of the zirconia-based material is within 0.1 μm to 0.5 μm, which is conducive to the formation of a stable ceramic layer 20, thereby forming a support for the porous structure 202. The coating did not crack or peel off after the open flame impact test by the flame gun, and the coating was not broken down during the insulation test.

[0144] Example 22 adjusted the composition of the glass slurry, thereby changing the linear thermal expansion coefficient of the glass layer 30. The coating did not crack or peel off during the open flame impact test with a flame torch, and the coating was not broken down during the insulation test.

[0145] Example 23 adjusted the composition of the glass slurry so that the linear thermal expansion coefficient of the glass layer 30 was not within the range of this application. The coating cracked and peeled off after an open flame impact test with a flame torch, and the coating was punctured during the insulation test.

[0146] The above provides a detailed description of a composite material provided in the embodiments of this application. Specific examples have been used to illustrate the principles and implementation methods of this application. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.

Claims

1. A composite material, characterized by, The composite material comprises: a base body (10); a ceramic layer (20) disposed on at least part of a surface of the base body (10); the ceramic layer (20) comprising a pore-forming agent (201); a glass layer (30) disposed on at least part of a side of the ceramic layer (20) away from the base body (10); wherein the pore-forming agent (201) is configured to be vaporized when reaching a first temperature T1; the glass layer (30) is configured to be at least partially converted into a glass body (301) in a molten state when reaching a second temperature T2, and T2>T1.

2. The composite material of claim 1, wherein, The first temperature T1 satisfies: 350℃≤T1≤450℃.

3. The composite material of claim 1, wherein, The second temperature T2 satisfies: 900℃≤T2≤1000℃.

4. The composite material of claim 1, wherein, The linear thermal expansion coefficient of the glass layer (30) is in the range of 13 x 10 -6 / K to 19 x 10 -6 / K; and / or, The linear thermal expansion coefficient of the ceramic layer (20) is in the range of 10 x 10 -6 / K to 12 x 10 -6 / K; and / or, The linear thermal expansion coefficient of the base body (10) is in the range of 10 x 10 -6 / K to 18 x 10 -6 / K; and / or, The base body (10) is made of metal.

5. The composite material of claim 1, wherein, The ceramic layer (20) has a thermal conductivity in a range of 2.0 W / m·K to 3.3 W / m·K.

6. A zirconia-based slurry characterized by: The zirconia-based slurry is used to prepare the ceramic layer (20) of the composite material according to any one of claims 1 to 5, and comprises, in terms of mass fraction: a zirconia-based material, 50 parts to 70 parts; a pore-forming material, 5 parts to 15 parts; a first solvent, 20 parts to 30 parts; a first binder, 3 parts to 5 parts.

7. The zirconia-based slurry according to claim 6, wherein: the zirconia-based material satisfies at least one of the following conditions: a) the zirconia-based material comprises one or more of zirconium dioxide, yttrium oxide stabilized zirconia, and scandium oxide stabilized zirconia; b) the crystal structure of the zirconia-based material comprises tetragonal phase and / or cubic phase; c) the particle size of the zirconia-based material is in a range of 0.1 μm to 0.5 μm.

8. The zirconia-based slurry according to claim 6, wherein: the pore-forming material satisfies at least one of the following conditions: d) the pore-forming material comprises one or more of corn starch and polymethyl methacrylate; e) the particle size of the pore-forming material is in a range of 0.3 μm to 0.5 μm.

9. The zirconia-based slurry according to claim 7, wherein: the zirconia-based slurry comprises, in terms of mass fraction: a pore-forming material, 8 parts to 13 parts; and / or, the particle size of the pore-forming material is in a range of 0.35 μm to 0.45 μm.

10. The zirconia-based slurry according to claim 6, wherein: the first solvent comprises water, or the first solvent comprises one or more of anhydrous ethanol, methyl ethyl ketone, toluene, xylene, isopropyl alcohol, and terpilenol; and / or, the first binder comprises one or more of polyvinyl butyral, polyvinyl alcohol, and ethyl cellulose.

11. A method of producing a composite material as claimed in any one of claims 1 to 5, characterised in that: The preparation method comprises: disposing a zirconia-based slurry on at least part of a surface of a base body (10) to form a ceramic layer (20); the thickness of the zirconia-based slurry is in a range of 20 μm to 200 μm; covering a glass paste on at least part of a side of the ceramic layer (20) away from the base (10) to form a glass layer (30); the thickness of the glass paste ranges from 50 μm to 300 μm; wherein the glass paste comprises, by mass fraction: an oxide, 60-80 parts; a second solvent, 15-35 parts; a second binder, 3-7 parts; a dispersant, 1-2 parts.

12. The method of claim 11, wherein: the oxide comprises a first oxide and a second oxide; wherein the glass paste satisfies at least one of the following conditions: f) the first oxide comprises one or more of calcium oxide, aluminum oxide, magnesium oxide; g) the second oxide comprises one or more of silicon oxide, sodium oxide, bismuth oxide, boron oxide, titanium oxide, cerium oxide, barium oxide, strontium oxide, lithium oxide, zinc oxide; h) the mass ratio of the first oxide to the second oxide ranges from (27-30):(33-39).

13. The method of claim 11, wherein: the second solvent comprises water, or the second solvent comprises one or more of anhydrous ethanol, methyl ethyl ketone, toluene, xylene, isopropyl alcohol, terpineol; and / or, the second binder comprises one or more of polyvinyl butyral, polyvinyl alcohol, ethyl cellulose; and / or, the dispersant comprises one or more of triethanolamine or polyacrylic acid.

Citation Information

Patent Citations

  • High-strength carbon-fiber-reinforced zirconia-ceramic-base composite material and preparation method thereof

    CN104876613A

  • Preparation method of zirconia ceramic with porous layer

    CN107686379A

  • Copper bar and battery pack

    CN113644388A

  • Flame-retardant heat-insulation fireproof material for battery

    CN115538175A

  • Method for preparing ceramic protective layer on surface of metal or alloy material, composite material and application of composite material

    CN118002452A